2012
DOI: 10.5307/jbe.2012.37.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production Potential of Food Waste and Food Waste Mixture with Swine Manure in Anaerobic Digestion

Abstract: Purpose: Methane production potential in aerobic digestion was assessed according to feed to inoculum (F/I) ratio for food waste only, and mixing ratio of two materials for food waste and swine manure to give a basic data for the design of anaerobic digestion system. Methods: Anaerbic digestion test was performed using a lab scale batch reactor at 35 o C for six different feed to inoculum (F/I) ratios (0.50, 0.72, 1.14, 1.50, 2.14 and 3.41), three food waste to swine manure ratios (100:0, 60:40 and 40:60) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Raposo et al (2009) observed stable digestion operation for TVFA/TA ratio in the range of 0.30-0.40 or less but at around TVFA/TA ratio of 0.70 destabilization of digester was observed. Similarly, Islam et al (2012) noticed TVFA/TA ratios as important criteria for judging stability in batch digesters during anaerobic co-digestion of food waste with SM. The VS removal for FW was found to be 77.3% which is similar as reported by Eiroa et al (2012) but lower than as reported by Chen et al (2010) (81%-95%) (Appendix 1).…”
Section: Biogas Productivity Of Fwmentioning
confidence: 99%
“…Raposo et al (2009) observed stable digestion operation for TVFA/TA ratio in the range of 0.30-0.40 or less but at around TVFA/TA ratio of 0.70 destabilization of digester was observed. Similarly, Islam et al (2012) noticed TVFA/TA ratios as important criteria for judging stability in batch digesters during anaerobic co-digestion of food waste with SM. The VS removal for FW was found to be 77.3% which is similar as reported by Eiroa et al (2012) but lower than as reported by Chen et al (2010) (81%-95%) (Appendix 1).…”
Section: Biogas Productivity Of Fwmentioning
confidence: 99%
“…While 6% to 8% increase in feed concentration decreased the conversion efficiency and at 10 % inhibition of the process occurred. Alike study of Islam et al (2012) also reported the methane production from food waste and its co-digestion with swine manure at 35 o C analyzing various feed to inoculum (F / I) ratios and food waste to swine manure mixtures ratios with the loading quantities of 0.01 ml / g VS and 0.03ml / g VS. The highest biogas yield of 1148 mL / g VS for the co-digesting ratio 40:60 at 0.01ml / g VS was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The CH 4 heat content is approximately 26.882 MJ/m 3 or 37.50 MJ/kg and has a density of 0.717 kg/m 3 . Islam et al (2012) and Dzene et al (2016) found that when 0.028 m 3 of biogas was burned, it yields about 2.52 kcal of heat energy per % CH 4 composition. If biogas is composed of 60% CH 4 , it will yield 5,400 kcal/ m 3 .…”
Section: Introductionmentioning
confidence: 99%